Catalytic CO oxidation over Pd70Au30(111) alloy surfaces: spectroscopic evidence for Pd ensemble dependent activity. Issue 94 (13th November 2017) - Toyoshima, Ryo; Hiramatsu, Nana; Yoshida, Masaaki; Amemiya, Kenta; Mase, Kazuhiko; Mun, Bongjin Simon; Kondoh, Hiroshi
Abstract : We report active Pd ensembles for catalytic CO oxidation over Pd70 Au30 (111) alloy surfaces by direct in situ spectroscopic observations. Abstract : Catalytic CO oxidation over Pd(111) and Pd70 Au30 (111) surfaces was investigated by in situ spectroscopic observations to understand the alloying effect. The reaction behaviour on Pd70 Au30 (111) is greatly different from that on Pd(111). Pd monomer and dimer ensembles can act as active centers, whereas triangular-shaped trimers and larger ensembles are inactive.